Internal control instruments in the accounting policy of public sector entities - Kanapickienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2013)
The main legal issues regarding internal control of a public legal entity are regulated by the Law of Internal Control and Internal Audit of the Republic of Lithuania (LR) which designates that one of the aims of internal control is to ensure the reliability and completeness of information and reports. The main regulatory enactments of accounting determine many instruments of internal control which must be ensured by the accounting policy adopted in a public sector entity. Regulatory enactments cover different spheres, i.e. accounting and internal control. These spheres are closely interrelated; therefore, it is important to examine the interrelations between the accounting policy and internal control system. The object of the research is internal control instruments in the accounting policy of public sector entities.The aim of the research is to examine the regulation of internal control instruments by legal acts with regard to the accounting policy of a public sector entity. The article provides the analysis of the accounting organization instruments and internal control instruments of accounting technique which are regulated by the Law of Accounting of LR (2001) and the Law of Public Sector Accountability of LR (2007). The paper systematizes the internal control instruments of accounting policy.
Keywords: internal control; accounting policy; public sector entity